The Green Entrepreneurship Behavior: A Literature Review - Maisaroh Maisaroh; Hunik Sri Runing Sawitri; Nor Hanuni Ramli (Universitas Muhammadiyah Magelang, 2022)
Research on green entrepreneurship behavior is still leaving questions related to the support against the grand theory that has been already acknowledged by academicians or practitioners. This article serves as a literature review of recent findings related to green entrepreneurship behavior variables reviewed from the underlying theories. Using content analysis from previous research articles, the researchers conducted a study that focused on the underlying theories and antecedents of the green entrepreneurship behavior variable. The article selection process is based on internationally reputed journals published over the past five years (2017-2021), searches on the Science Direct web, using the keywords 'green entrepreneurship', 'sustainable entrepreneurship', 'ecopreneurship', environment entrepreneurship, and 'antecedents'. The results showed that there are various theoretical concepts that can be used to explain and determined the antecedents of green entrepreneurship behavior. This includes psychological, personality traits, and contextual factors that were identified as antecedents of green entrepreneurship behavior. For further research, there are many related issues that can be analyzed, such as the decision-making process to become green entrepreneurs, the implementation of green entrepreneurship practices, etc.